Role of Audit Committees and Board of Directors in Reducing Earning Management of Companies Listed in Tehran Stock Exchange - Khosheghbal, Marzieh; Amiri, Ali; Homayoon, Ali (International Journal of Economics and Financial Issues, 2017)
The purpose of this study was to examine role of audit committees and board of directors in reducing earning management of companies listed in Tehran Stock Exchange. In this research, audit committees and board of directors were selected as independent variable and earning management as dependent variable. Statistical population of study consisted of all companies listed in Tehran Stock Exchange during 2009-2014 selecting manufacturing companies with available data listed in stock market during 2009-2014 as sample companies. To estimate research models, generalized least squares (GLS) method was employed and to test independency of regression model’s error, Durbin–Watson test was used. Significance of regression model was examined using F value; t-student value was used to confirm or reject research hypotheses through Eviews Software. Results of research showed a positive relationship between firm size and earning management; while there was not any relationship between board size, independence of board of directors, audit committee and earning management. Keywords: Earning Management, Board Size, Firm Size, Independence of Board of Directors, Audit Committee JEL Classifications: L25, M4